2005
DOI: 10.1897/04-216r.1
|View full text |Cite
|
Sign up to set email alerts
|

Copper uptake by Mytilus edulis in the presence of humic acids

Abstract: The effects of humic acids (HA) on Cu uptake by the blue mussel (Mytilus edulis) were studied in chemically defined seawater. Short-term uptake by excised gills was studied and compared with whole-mussel Cu accumulation. Copper uptake in gills is not a saturable process within the time frame and concentration range tested, being a linear function of time (0-120 min) and Cu concentration (0-150 microg/L). For the whole mussel, Cu uptake is not linear with time (0-72 h) and Cu concentration (0-130 microg/L). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 34 publications
4
28
1
2
Order By: Relevance
“…Copper, cadmium and mercury were obtained by dissolving CuCl 2 · 2H 2 O, CdCl 2 · H 2 O and HgCl 2 in chemically defined artificial seawater (ASW), made up from analytical grade reagents and Milli-Q water following the formulation of Lorenzo et al (2005). Preliminary trials showed no significant differences in hatching success when using 0.22 μm filtered natural seawater (FSW) compared with ASW.…”
Section: Experimental Solutions and Exposuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Copper, cadmium and mercury were obtained by dissolving CuCl 2 · 2H 2 O, CdCl 2 · H 2 O and HgCl 2 in chemically defined artificial seawater (ASW), made up from analytical grade reagents and Milli-Q water following the formulation of Lorenzo et al (2005). Preliminary trials showed no significant differences in hatching success when using 0.22 μm filtered natural seawater (FSW) compared with ASW.…”
Section: Experimental Solutions and Exposuresmentioning
confidence: 99%
“…Naphthalene exposures were conducted at the nominal concentrations 15.75, 31.5, 62.5, 125, 250 and 500 μg L −1 , fluoranthene and phenanthrene exposures at 6.25, 12.5, 25, 50, 100 and 200 μg L −1 , and pyrene at 1.25, 2.5, 5, 10, 20 and 40 μg L −1 . The experimental concentrations were obtained by diluting the DMSO-stock solutions in ASW, as prepared in Lorenzo et al (2005). The stock solutions were prepared daily and stored at room temperature in the dark.…”
Section: Experimental Solutions and Exposuresmentioning
confidence: 99%
“…Lower cytosolic Cu concentration in samples from location H could be at least partially explained by the very low salinity at this location due to its position in the estuary. Owing to the fact that Cu binding to the dissolved organic matter increases when the salinity decreases (Lores and Pennock, 1998) a large proportion of Cu could have been bound to the organic matter which would decrease the Cu uptake (Lorenzo et al, 2005) and consequently the bioaccumulation in bivalves. Except for Cu dissolved organic matter has significant role also in Pb speciation in the seawater.…”
Section: Discussionmentioning
confidence: 99%
“…Humic acids increased (García-Mina et al, 2004;Lorenzo et al, 2005) or decreased (Kungolos et al, 2006) the uptake of Cu by plant were observed. The results in Table 3 showed that the exchangeable fraction of Cu dropped under higher concentration of Cu treatments (!414 mg kg À1 DW) with the addition of humic acids, and carbonate bound fraction decreased in treatments.…”
Section: Phytoextraction Of Cu By E Nuttalliimentioning
confidence: 95%